Diagnostic Accuracy of Computed Tomography in Predicting Primary Aldosteronism Subtype According to Age - Lee, Seung Hun (Endocrinol Metab (Seoul), 2021)
BACKGROUND: Guidelines by the Endocrine Society Guideline on bypassing adrenal vein sampling (AVS) in patients <35 years old with marked primary aldosteronism (PA) (hypokalemia and elevated plasma aldosterone concentration [PAC]) and a unilateral lesion on computed tomography (CT) are based on limited number of studies. We aimed to determine the accuracy of CT in PA patients according to age. METHODS: In this retrospective study, we investigated the concordance between CT and AVS in 466 PA patients from two tertiary centers who successfully underwent AVS. RESULTS: CT had an overall accuracy of 64.4% (300/466). In the group with unilateral lesion, patients with hypokalemia had higher concordance than those without hypokalemia (85.0% vs. 43.6%, P<0.001). In the group with marked PA (hypokalemia and PAC >15.9 ng/dL) and unilateral lesion, accuracy of CT was 84.6% (11/13) in patients aged <35 years; 100.0% (20/20), aged 35 to 39 years; 89.4% (59/66), aged 40 to 49 years; and 79.8% (79/99), aged ≥50 years. Cut-off age and PAC for concordance was <50 years and >29.6 ng/dL, respectively. The significant difference in accuracy of CT in 198 patients with marked PA and a unilateral lesion between the <50-year age group and ≥50-year age group (90.9% vs. 79.8%, P=0.044) disappeared in 139 of 198 patients with PAC > 30.0 ng/dL (91.9% vs. 87.7%, P=0.590). CONCLUSION: Patients with hypokalemia, PAC >30.0 ng/dL, and unilateral lesion were at high risk of unilateral PA regardless of age.